Propiolated castor oil: A novel and highly versatile bio-based platform for extremely fast, catalyst-, and solvent-free amino-yne click reactions - ÇAKMAKÇI, EMRAH (My University, 2023)
The quest for sustainable monomers and \"green\" synthetic pathways for the design, fabrication, and modification of various polymers is of great importance and attracts a great deal of attention. Here, a highly versatile and novel bio-based platform was developed by reacting castor oil with propiolic acid for performing amino-yne click reactions. Owing to the electron-deficient nature of the propiolic acid esters, amino-yne click reactions were conducted with ease at room temperature, in the absence of any catalyst and solvent (as long as the amines were low-viscosity liquids at room temperature), and within 5 min. Several primary and secondary amines were shown to react readily with the developed platform. Furthermore, thermosets were prepared by using the propiolated castor oil and multifunctional amines. The prepared thermosets displayed improved thermal properties and elastomer-like mechanical properties.
Keywords: Tarımsal Bilimler; Kimya Mühendisliği ve Teknolojisi; Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Chemical Engineering and Technology; Chemistry; Biochemistry; Alcaloides; Natural Sciences; Engineering and Technology; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); YEŞİL VE SÜRDÜRÜLEBİLİR BİLİM VE TEKNOLOJİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); MÜHENDİSLİK, KİMYASAL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); GREEN & SUSTAINABLE SCIENCE & TECHNOLOGY; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); ENGINEERING, CHEMICAL; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Mühendislik (çeşitli); Kimya (çeşitli); Genel Kimya; Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Fizik Bilimleri; General Engineering; Engineering (miscellaneous); Chemistry (miscellaneous); General Chemistry; Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Physical Sciences; green chemistry; aza-Michael; amino-yne click reactions; castor oil; propiolic acid; activated alkyne; POLYMERIC MATERIALS; VEGETABLE-OILS; POLYESTER